Avaliaç\~ao dos impactos regionais do Programa Nacional de Agricultura Familiar (PRONAF) - César Nunes de Castro; Guilherme Mendes Resende; Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The aim of this paper is to evaluate the regional impacts of the National Family Farming Program (PRONAF in the Portuguese acronym) between 2000 and 2010, using the econometric instrumental panel data models with fixed effects. The approach combined impact assessments at various regional scales - local, microrregional and mesorregional. Additionally, impact assessments for each of the five Brazilian regions were separately carried out. While in the Northeast, Southeast and South regions it was possible to verify the Program's positive impacts on per capita gross domestic product (GDP) and municipal agricultural GDP growth rates, the North and Midwest regions were characterized by the absence of impacts related to the Program. The magnitude of the impacts was higher in southern and southeastern regions than in the Northeast. This demonstrates the importance of conducting a regional analysis even in nationwide policies. Finally, the impact assessments in microrregional and mesorregional levels showed results qualitatively similar to those observed at the municipal level. We conclude, therefore, there were positive impacts on GDP per capita and agricultural GDP growth rates due to PRONAF in all three analyzed scales for the Northeast, Southeast and South regions. It is noteworthy that, during the period considered for this study (2000-2010), these three regions concentrated 84.4% of the program's resources and 90.4% of the program's beneficiaries.
Keywords: C23; O18; Q18; 330; impact evaluation; family farming; PRONAF; public policies; regional development